Developments in the study and applications of bacterial transformations of selenium species. (16th November 2020) - Ojeda, Jesus J.; Merroun, Mohamed L.; Tugarova, Anna V.; Lampis, Silvia; Kamnev, Alexander A.; Gardiner, Philip H. E.
Abstract: Microbial bio-transformations of the essential trace element selenium are now recognized to occur among a wide variety of microorganisms. These transformations are used to convert this element into its assimilated form of selenocysteine, which is at the active center of a number of key enzymes, and to produce selenium nanoparticles, quantum dots, metal selenides, and methylated selenium species that are indispensable for biotechnological and bioremediation applications. The focus of this review is to present the state-of-the-art of all aspects of the investigations into the bacterial transformations of selenium species, and to consider the characterization and biotechnological uses of these transformations and their products.